Crack Extension Resistance of Normal-Strength Concrete Subjected to Elevated Temperatures - Jing Chen; Zhoudao Lu (Advances in Materials Science and Engineering)
Determination of the residual crack extension resistance curves (KR-curves) associated with cohesive force distribution on fictitious crack zone of complete fracture process is implemented in present research. The cohesive force distributes according to bilinear softening traction-separation law proposed by Petersson. Totally ten temperatures varying from 20°C to 600°C and the specimen size of 230×200×200 mm with initial-notch depth ratios 0.4 are considered. The load-crack mouth opening displacement curves (P-CMOD) of postfire specimens are obtained by wedge-splitting method from which the stress intensity factor curves (K-curves) are calculated. In each temperature, with the distribution of cohesive force along the fracture process zone, the residual fracture toughness KR (Δa) increases with increasing crack length Δa, whereas the KR-curves decrease with increasing temperatures Tm for the thermal damage induced. The stability analysis on crack propagation demonstrates that when the residual KR-curve is higher than K-curve, the crack propagates steadily; otherwise, the crack propagates unsteadily.